CODE MIXING ANALYSIS IN THE CAPTIONS OF @PADULIANJING INSTAGRAM ACCOUNT (A SOCIOLINGUISTIC STUDY) - Dicky Rachmat Ramdhani (ReALL - Research on Applied Linguistics and Literature, 2022)
This study is entitled â€œCode Mixing Analysis in The Captions of @padulianjing Instagram Accountâ€. It focuses on finding the kinds of code mixing supported by the theory from Pateda (1992) and explaining the factors of code mixing occurrence supported by the theory from Hoffman (1991). This study is a qualitative descriptive study. The researcher collects the data of 30 post captions from September 2018 until April 2019 by observation and documentation techniques. The result shows: 1) the kinds of code mixing occurs in the form of word, phrase, clause, baster, repetition, and idiom; and 2) there are six factors of code mixing occurrence namely when talking about a particular topic, when quoting someoneâ€™s statements, when showing empathy & sympathy, when inserting a sentence connector, when trying to attract othersâ€™ attention, and when having limited vocabularies. In conclusion, there are 6 forms of code mixing and 6 factors lead the code mixing. It is recommended for the further researchers to do interview when investigate the same research object.